Judge Frank Creede, Jr. Swears In Superior Court Judge Mario Olmos - Watkins, Howard::::::::: (1983)
Judge Frank Creede, Jr. and Judge Mario Olmos shaking hands; Mary Louise Frampton smiling and holding Margaret Olmos, Mario's parents, Delores Olmos and Fidel Olmos; son Daniel looking away Law Offices of Olmos and Frampton at 925 N St. #150, Fresno